Research on the Effectiveness of Black-Faced Spoonbill Bird Tourism and Conservation Strategy. A Case Study of Shifen Community at Chi-Gu District of Tainan City - HUANG, Chih-Jan; YANG, Yung-Nane (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021DO - 10.14505//jemt.v12.2(50).01, 2021)
In this study, the concept of ecotourism serves as the framework for the investigation of black-faced spoonbill tourism and conservation strategies implemented in Shifen, a community in the Chi-Gu District of Tainan City. It featured an examination of the formulation, planning, and implementation of the conservation strategies and conducted in-depth interviews on individuals from the public sector, local residents, tourists, and nongovernment organizations. Research results identified numerous problems: latent concerns regarding black-faced spoonbills as a tourism resource, poor awareness of ecotourism, difficulties in implementing black-faced spoonbill tourism and conservation strategies, and difficulty maintaining a balance between conservation and residents’ livelihoods. The government is advised to integrate the opinions and suggestions of local residents, promote community participation, and increase job opportunities for local residents to create a win-win model for the development of community-based ecotourism.